PENERAPAN METODE QFD (QUALITY FUNCTION DEPLOYMENT) DI UD GARUDA MOTOR JAJAG, BANYUWANGI - Giovani Hartanto Ardian U.; Stefanus Budy Widjaja S.; Fitri Novika Widjaja (CALYPTRA, 2018)
Abstract- In order to upgrade the quality if services in UD Garuda Motor Jajag, the research done by implementing Quality Function Deployment (QFD). The purpose of Quality Function Deployment (QFD) implementation is to get the Voice of Customer, Technical Response Actions Priority, as well as strategies that resulted in the proposal should be taken bt the company to improve service quality. Based on research conducted using the method Quality Function Deployment (QFD) which implemented to service quality, occurred five dimension of service quality (tangible, assurance, reliability, responsiveness, and emphaty) and concluded technical respons actions (replace workshop obsolete tools and adapt new tools, open new more strategic bussiness branch, implement already made SOP, create new queue system using numbers, conduct training problem solving and FAQ explanation to employees, hire software developer, imposing maximum waiting time, increase communication of sales department and other department, hold additional meeting for employees, and implementation of company vision and mission). From the calculations, can be seen that all the technical response from the company haven’t met the desired value and needs to be improved, in order to improve service quality in UD Garuda Motor Jajag.